2018
DOI: 10.5539/ijel.v8n5p205
|View full text |Cite
|
Sign up to set email alerts
|

English for Doctors: An ESP Approach to Needs Analysis and Course Design For Medical Students

Abstract: English is considered a language of communication as well as language of fashion and status in Pakistan. For last some decades, it is being taught in different institutions to meet specified academic and professional needs of learners. As far as medical profession is concerned, doctors need English language during their academic studies as well as in their professional settings. The study investigated the communicative needs of doctors at academic and professional level in survey based research. The data was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 6 publications
2
12
0
2
Order By: Relevance
“…Furthermore, the data also stated that the communication or interaction skill of a doctor is important because it will influence the way patient connect with them and trust them. This result also shared the same idea with two studies conducted by Kayaoğlu andAkbaş in 2016 andLodhi et al in 2018. Both studies explained the importance of interaction or communication skill for medical students during their study. Both studies emphasize on the importance of interaction to boost the students' skill for their future career as a medical worker or doctor.…”
Section: Target Situation Analysissupporting
confidence: 86%
See 1 more Smart Citation
“…Furthermore, the data also stated that the communication or interaction skill of a doctor is important because it will influence the way patient connect with them and trust them. This result also shared the same idea with two studies conducted by Kayaoğlu andAkbaş in 2016 andLodhi et al in 2018. Both studies explained the importance of interaction or communication skill for medical students during their study. Both studies emphasize on the importance of interaction to boost the students' skill for their future career as a medical worker or doctor.…”
Section: Target Situation Analysissupporting
confidence: 86%
“…Therefore, once ESP (English for Specific Purposes) concept was proposed by Hutchinson and Waters back in 1987 after the World War II, people tended to create or design a specific course for medical students called Medical English (ME). Medical English mainly focuses at the technical and contextual based (Lodhi, Shamim, Robab, Shahzad, & Ashraf, 2018). Also, ME is categorized as extremely different with general English that has been existed since the beginning of the spread of English because eventually ME is strongly related to medical workers' needs and is directly connected with their future skill.…”
Section: Introductionmentioning
confidence: 99%
“…A number of research studies have reported that English at Higher Education becomes one of determining factors of ones' success in both academic and career (Antony, 2018;Daffa-Allah, 2012;Kaur, 2007;Lodhi, Shamim, Robab, Shahzad, & Ashraf, 2018); Poorhadi, 2017;Skelton & Whetstone, 2012;Woodrow, 2018). These studies are aligned with the previous studies conducted by Sujana, Fitriana & Syahrial (2016) and Sujana, Hanafi, Wilian, Syahrial, & Fitriana (2019).…”
Section: Introductionmentioning
confidence: 99%
“…A kommunikációs készségek erősítése éppen ezért elengedhetetlen és kiemelt fontosságú. Módszertanilag számos eszköz fellelhető a szaknyelvi órákon, például a mondatfordítás vagy a szókincs gyakorlása különféle módokon, de legtöbbször a feladat-és problémaközpontúság jellemző rájuk (Lodhi et al, 2018), mivel a hallgatók aktív bevonása pozitív hatással lehet a motivációjukra, még a kevésbé érdekes feladatok esetében is (Ryan -Deci, 2000).…”
Section: Bevezetésunclassified